Benefactor or burden: Exploring the professional identity of safety professionals. (September 2018) - Provan, David J.; Dekker, Sidney W.A.; Rae, Andrew J.
Abstract: Introduction: The professional identity of safety professionals is rife with unresolved contradictions and tensions. Are they advisor or instructor, native or independent, enforcer of rules or facilitator of front-line agency, and ultimately, a benefactor for safety or an organizational burden? Perhaps they believe that they are all of these. This study investigated professional identity through understanding what safety professionals believe about safety, their role within organizations, and their professional selves. Understanding the professional identity of safety professionals provides an important foundation for exploring their professional practice, and by extension, understanding organizational safety more broadly. Method: An embedded researcher interviewed 13 senior safety professionals within a single large organization. Data were analyzed using grounded theory methodology. The findings were related to a five-element professional identity model consisting of experiences, attributes, motives, beliefs, and values, and revealed deep tensions and contradictions. This research has implications for safety professionals, safety professional associations, safety educators, and organizations. Highlights: Career pathway is the dominant factor in determining safety professional identity. Interpersonal skills and relationships trade-off with technical skills and authority. Safety bureaucracy is an encumbrance on safety and safety professionals. Safety professionals confuse their role in decision-making with line managers. Safety professionals have a moral and ethical motivation for their role.